Keluarga dan Rumah Tangga: Satuan Penelitian dalam Perubahan Masyarakat - Achmad Fedyani Saifuddin (Antropologi Indonesia, 1999)
Family and household are two concepts that have been blended into a single notion in most of the texts on kinship and social organization in the past, because, in many instances, they have interchangeably functions in many developed societies in which nuclear family type is the main reference. But, this situation is much different if we approach our developing societies-with special emphasis, urban-in terms of vastly and hardly social and economic changes. This article proposes to distinguish family and household concepts for analytical purposes. Household in its flexible form provides more promising space for dynamic anthropological research, especially in our society than the classical family concept. Selecting household as a common focus for anthropological research and analysis has both practical and theoretical justifications.